Understanding Anthropometry, Metabolism and Menstrual Status of Japanese College Female Long-distance Runners - Iwamoto, S; Sugita, K; Ishikawa-Takata, K; Kagawa, M; Ota, M; Suzuki, T; Hume, P (IOR Press, 2021)
Aim: To understand the anthropometry, metabolism, and menstrual status of Japanese collegiate female long-distance runners. Methods: This was a cross-sectional study of 29 Japanese college female long-distance runners divided into three menstruation status groups: 1) Regular; 2) Irregular; and 3) Amenorrhea. The amenorrhea group was further divided into participants who consulted a gynecologist and those who did not. Metabolism was measured using resting metabolic rate, total energy expenditure, and physical activity level. Energy was measured using energy intake, exercise energy expenditure, and energy availability (EA). Anthropometric measurements were performed following standardized techniques from the International Society for the Advancement of Kinanthropometry. Results: Of the 29 runners, 68% had menstrual dysfunction. The amenorrhea group who had consulted a gynecologist had lower body mass index (BMI) and lower skinfolds than the other groups. All groups had more than 30 kcal/kg fat free mass/day for EA with no difference between the groups. Conclusions: There was high prevalence of menstrual dysfunction in the female Japanese college long-distance runners. Runners with amenorrhea had lower BMI and lower skinfolds than the other groups, despite having consulted a gynecologist for medical support. All the runners had an energy deficiency higher than the published threshold; therefore, this threshold did not differentiate the amenorrhea or irregular menstruating athletes from regular menstruating athletes. Longitudinal tracking of athletes should include measurement of height, body mass, and skinfolds to enable evaluation of BMI, the sum of eight skinfold sites, and leanness ratio score as possible indicators over time for menstrual dysfunction.
Keywords: Female long-distance runners; Metabolism; Energy availability; Menstrual dysfunction; Anthropometry